Tracing modernity in the popular romances of the early republican period (1930-1945): the novels of Kerime Nadir, Esat Mahmut Karakurt and Muazzez Tahsin Berkand - Özkurt, Kerem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This thesis seeks to unearth the modernity discourse in the popular romance novels of Kerime Nadir, Esat Mahmut Karakurt and Muazzez Tahsin Berkand published during the period between 1930 and 1945. The analysis of these novels is made within a cultural context in which the similarities and differences of the novels are examined along with the literary production and consumption mechanisms of the period. This context is related to a global trend, the rise of the popular romance novels that narrate the social change, which was brought about the interwar modernity, over the man-woman relations in most part of Europe. In this framework, it is observed that modernity narrated in the popular romance novels studied here indicates a different modernity discourse than that exists in the canonical novels. This discourse of the popular romance novels, which is welcomed by the re-emerging middle class in the early Republican period, approaches modernity in a more positive manner and signals an intrinsic social change.
Keywords: Turkish fiction -- History and criticism.; Romances -- History and criticism.; Romance fiction -- History and criticism.